The regulatory mechanism and potential application of IL-23 in autoimmune diseases - Xiong, De-Kai; Shi, Xiang; Han, Miao-Miao; Zhang, Xing-Min; Wu, Na-Na; Sheng, Xiu-Yue; Wang, Ji-Nian (Frontiers in Pharmacology, 2022)
IL-23 is a heterodimeric pro-inflammatory cytokine secreted by dendritic cells and macrophages that belongs to the IL-12 family. It has pro-inflammatory effects and is a key cytokine and upstream regulatory cytokine involved in protective immune responses, stimulating the differentiation and proliferation of downstream effectors such as Th17 cells. It is expressed in various autoimmune diseases such as psoriasis, SLE, RA. The IL-23/TH17 axis formed by IL-23 and TH17 has been confirmed to participate in autoimmune diseases pathogenesis. IL-23R is the receptor for IL-23 and plays an activating role. Targeting IL-23 is currently the main strategy for the treatment of various autoimmune diseases. In this review we summarized the mechanism of action and clinical application potential of IL-23 in autoimmune diseases by summarizing the latest research results and reviewing the literature, which would help to further understand IL-23 and provide a theoretical basis for future clinical targeting and drug development.